Sayyid Qutb’s Concept of Da’wah in His Fi Zilal al Quran - Ahmad Zabidi (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2020)
This research aims to describe concept and method of da’wah in Sayyid Qutb’s perspective specially in his work on tafsir, Fi Zilal al-Qur'an. The research was conducted by exploring the concept of da’wah theoretically and its implications in dealing with contemporary problem of da’wah. This study employs qualitative approach with content analysis technique and library study method. The result shows that according to Sayyid Qutb understanding, Da’wah is an effort of the believers to realize the Islamic teaching in daily life. Also, da’wah is interpreted as a believer's effort to strengthen Allah SWT's teachings in human life. Sayyid Qutb’s Da’wah method is based on the interpretation of normative sources and historical facts that refer to efforts to preach based on human nature through tenderness, compassion, and good morals. This kind of da’wah conception has impact at the individual, family, community, and community levels in achieving happiness in this world and the hereafter.Penelitian ini bertujuan untuk mendeskripsikan konsep metode dakwah Sayyid Qutb dalam tafsir fī Zilāl al-Qur’an. Penelitian dilakukan dengan menggali konsep dakwah secara teoritik dan implikasinya dalam menjawab problematika dakwah kontemporer. Penelitian menggunakan pendekatan kualitatif dengan metode analisis isi. Hasil penelitian menunjukkan bahwa Sayyid Qutb memahami dakwah sebagai usaha orang beriman untuk mewujudkan sistem ajaran Islam dalam kehidupan. Selain itu, dakwah dimaknai sebagai usaha orang beriman untuk mengokohkan ajaran Allah Swt dalam kehidupan. Metode dakwahnya didasarkan pada penafsiran terhadap sumber normatif dan fakta historis yang merujuk pada fitrah manusia melalui kelembutan, kasih sayang dan akhlakul karimah. Implikasi praktis dakwah Islam berlangsung baik pada level individu, keluarga, masyarakat dan umat untuk mencapai kebahagiaan di dunia dan akhirat.